Perlindungan Hukum Terhadap Tenaga Kerja Indonesia di Luar Negeri - Ni Kadek Sintia Dewi; Desak Gde Dwi Arini; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Indonesian Workers, hereinafter referred to as TKI, are every Indonesian citizen who meets the requirements to work abroad in employment relations for a certain period of time by receiving wages. In the case of the placement of overseas Indonesian Workers held by Indonesian Manpower Services Companies must be in accordance with the terms and procedures specified in the legislation. After the terms and procedures are fulfilled, a work agreement is made concerning legal protection for the rights of Indonesian Workers. With the employment agreement, Indonesian Workers who work abroad will receive legal protection at pre-placement, placement and after-placement. The problem in this study is regarding the regulation of employment agreements and placement of Indonesian workers abroad and forms of legal protection for Indonesian workers abroad. The research method used in the discussion of this paper, the authors use the main approach, namely the Statute Approach and the Conceptual Approach as supporting the legislative approach, the source of the legal material for writing is obtained from the literature with the type of legal material in the form of material primary law and secondary legal material. The results of this study found that the weak protection of Indonesian workers is due to two main factors, namely the implementation factor of the protection law issued by the government does not work as it should, and a weak coordination factor between related stakeholders.